Health Workers' Legal Protection Policy to the Coronavirus Disease 19 (Covid-19) Containment Measures - Helmi Helmi; Hafrida Hafrida; Retno Kusniati (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
This research aims to analyze protection policies for health workers amidst COVID-19. Through statute approach and based on the rights theory, this study examines legal development, or legal framework is needed to formulate and to protect health worker. Since the COVID-19 outbreak spreads quickly and massively, Health worker is at the forefront of handling COVID-19, but they are also vulnerable to get infected by the virus. Some cases showed that many health workers tested positive after providing health services. The findings of the research showed that the right of medical workers to get personal protective equipment and safety guarantees were not enough to protect them. On the other hand, the community was still ignoring the risk of this disease and broke the health protocol in the public place. Health workers can perform their job effectively if people are in healthy condition and do not need to go to the hospital. To containment measures of the COVID-19 State has to choose one of the effective ways to protect people and health workers by regulating and giving a penalty to the perpetrators of the COVID-19 protocol.